Dense wavelength division multiplexing (DWDM) transmission system with optical amplifiers in cascade - Mahmud, S M Nazmul; Talukdar, Abdul Aoual (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.